China’s landscape in oncology drug research: perspectives from research collaboration networks - You, Han (Chin J Cancer Res, 2015)
OBJECTIVE: Better understanding of China’s landscape in oncology drug research is of great significance for discovering anti-cancer drugs in future. This article differs from previous studies by focusing on Chinese oncology drug research communities in co-publication networks at the institutional level. Moreover, this research aims to explore structures and behaviors of relevant research units by thematic community analysis and to address policy recommendations. METHODS: This research used social network analysis to define an institutions network and to identify a community network which is characterized by thematic content. RESULTS: A total of 675 sample articles from 2008 through 2012 were retrieved from the Science Citation Index Expanded (SCIE) database of Web of Science, and top institutions and institutional pairs are highlighted for further discussion. Meanwhile, this study revealed that institutions based in the Chinese mainland are located in a relatively central position, Taiwan’s institutions are closely assembled on the side, and Hong Kong’s units located in the middle of the Chinese mainland’s and Taiwan’s. Spatial division and institutional hierarchy are still critical barriers to research collaboration in the field of anti-cancer drugs in China. In addition, the communities focusing on hot research areas show the higher nodal degree, whereas communities giving more attention to rare research subjects are relatively marginalized to the periphery of network. CONCLUSIONS: This paper offers policy recommendations to accelerate cross-regional cooperation, such as through developing information technology and increasing investment. The brokers should focus more on outreach to other institutions. Finally, participation in topics of common interest is conducive to improved efficiency in research and development (R&D) resource allocation.